A participatory approach to assess the effectiveness of responses to cope with flood risk - Lucia Ceccato; Valentina Giannini; Carlo Giupponi (Fondazione Eni Enrico Mattei (FEEM), 2010)
This work illustrates the preliminary findings of a participatory research process aimed at identifying responses for sustainable water management in a climate change perspective, in two river basins in Europe and Asia. The paper describes the methodology implemented through local workshops, aimed at eliciting and evaluating possible responses to flood risk. Participatory workshops allowed for the identification of four categories of possible responses and a set of nine evaluation criteria, three for each of the three pillars of sustainable development. The main outcome of such activities consists in the ranking of broad response categories instrumental to the objective of the Brahmatwinn research project, i.e. the identification of Integrated Water Resource Management Strategies (IWRMS) based upon the issues and preferences elicited from local experts. The mDSS tool was used to facilitate transparent and robust management of the information collected through Multi-Criteria Decision Analysis (MCDA) and communication of the outputs.
Keywords: C61; Q01; Q54; Q56; Q58; 330; Participatory Process; Climate Change; Flood Risk; Decision Support System; Multi Criteria Analysis; MCA; Eliciting Responses; Evaluating Responses; Integrated Water Resources Management; IWRM; Mulino Decision Support System; mDSS; Umweltpolitik; Wasserbau; Überschwemmung; Umwelt-Informationssystem; Multikriteria-Verfahren; Südasien; Europa